PENGARUH DIGITAL MARKETING DAN BRAND AWARENESS TERHADAP PEMBELIAN PRODUK MAKANAN SUKLA PADA UMKM SATYAGRAHA DI KOTA DENPASAR - Dewa Ayu Sinta Dewi; Ni Luh Ketut Ayu Sudha Sucandrawati; Ni Putu Andini Desiyanti Laksmi (Nusantara Hasana Berdikari, 2022)
This study aims to determine the effect of Digital Marketing on the Purchase of Sukla Food Products, to determine the effect of Brand Awareness on the Purchase of Sukla Food Products and to determine the effect of Digital Marketing and Brand Awareness on the Purchase of Sukla Food Products at Satyagraha SMEs in Denpasar City. The type of research used is survey research and uses a quantitative approach. This research was conducted on three Satyagraha SMEs in Denpasar City, namely Babi Guling Golden SMEs, Babi Guling Nojas SMEs and Babi Guling Ocha SMEs. The number of samples as many as 83 respondents, determined by non-probability sampling method and purposive sampling technique. Respondents from this study were consumers or Hindu communities who had bought Sukla Babi Guling food at Satyagraha SMEs in Denpasar City. Sources of data using primary data and secondary data. Methods of data collection using observation, interviews, questionnaires and literature study. The data analysis technique uses Descriptive Analysis, Multiple Linear Regression Analysis, Classical Assumption Test, Coefficient of Determination and t test and F test. Data processing uses SPSS software program.The results of this study indicate that partially digital marketing has a positive and significant influence on the purchase of sukla food products and brand awareness has a positive and significant influence on the purchase of sukla food products. Simultaneously digital marketing and brand awareness have a positive and significant influence on the purchase of sukla food products.